(untitled) (World Bulletin of Public Health, 2022)
A laser is a perfect therapeutic option utilized in a variety of medical fields, including reproduction for better spermatozoa preparation and activation for improving spermatozoa activity and motility, and with the indirect swim-up procedure to reduce any round cells and leukocytes from the sample